Gendered Expectations: Strategies for Navigating Structural Challenges in Support of Transgender and Nonbinary Trainees in Academic Medicine. (May 2020) - Cook, Tiffany E.; Dimant, Oscar E.; Novick, Rebecca; Adegbola, Adetoro; Blackstock, Uché; Drake, Carolyn B.; Patenaude, Mason E.; Ravenell, Joseph E.; Radix, Asa; Greene, Richard E.
Abstract : Members of the lesbian, gay, bisexual, transgender, and queer community experience marginalization, bias, and discrimination, including in the world of academic medicine. People who are transgender and nonbinary (TGNB) experience further marginalization compared with individuals who are lesbian, gay, bisexual, and queer. According to a recent survey, more than half of medical students who are TGNB chose not to disclose their gender identities during training due to fears of discrimination, feeling a lack of support, and concerns about future career options. Academic medicine has historically pathologized TGNB individuals, perpetuating discrimination structurally and reinforcing discriminatory behaviors of peers and faculty. In this Perspective, the authors provide a comprehensive overview of the challenges that administrators and educators face in creating a learning environment that is inclusive of TGNB trainees. They outline opportunities for change and provide strategies to address administrative and educational challenges, including those related to institutional climate, policies, data collection, physical spaces, health care, curriculum, mentoring, and the evaluation of TGNB trainees. Finally, the authors issue a call to action for medical educators and administrators to create environments in which trainees who are TGNB can fulfill their educational mission: to learn the practice of medicine.